Transgenic plants as edible vaccines — reality and future prospects - Domansky, N.N. (Биополимеры и клетка, 1999)
This review describes the recent progress in the construction of transgenic plants for vaccine production Transgenic plants are an attractive and cost-effective alternative to microbial systems for the production of proteins with pharmaceutical value. Advances in biotechnology are enabling plants to be exploited the expression of candidate vaccine antigens with the goal of using the edible plant organs for economical delivery of oral vaccines. It has recently been shown that genes encoding antigens of bacterial and viral pathogens can be expressed in plants in a form in which they retain native immunogenic properties. Transgenic potato tubers expressing bacterial antigens stimulated humoral and mucosal immune response; when they were provided as a food. Although the utility of «edible vaccines» to prevent disease remains to be established, the successful implementation of this strategy can be the first step on the way to modern vaccines of new generation. Огляд сучасних літературних даних про створення трансгенних рослин для виробництва вакцин. Трансгенні рослини ни є дуже привабливою та дешевою альтернативою існуючим мікробіологічним системам виробництва білків для фармацевтики. Успіхи сучасної біотехнології відкрили можливість експерсувати у рослинах різні антигени, що використовуються для вакцинації, з метою використання їстівних частин рослий длятранспорту оральних вакцин. Було продемонстровано, що гени, котрі кодують антигени бактеріальних та вірусні – патогенів, можуть бути експресовані у рослинах із збереженням їхніх природних імунологічних властивостей. Гак, бульби трансгенної картоплі, що експресували бактеріальні антигени, стимулювали гуморальну та мукозну імунні відповіді при використанні їх у їжу. Хоча використання їстівних вакцин для запобігання хвороб ще не доведене, подальшій розробок цього напряму може стати першим кроком на шляху до вакцин нової генерації Обзор современных литературных данных о создание трансгенных растений для производства вакцин. Трансгенные растения являются весьма привлекательной и дешевой альтернативой существующим микробиологическим системам производства белков для фармацевтики. Успехи современной биотехнологии открыли возможность экспрессировать в растениях различные антигены, используемые при вакцинации, для применения съедобных частей растений при транспорте оральных вакцин. Было продемонстрировано, что гены, кодирующие антигены бактериальных и вирусных патогенов, могут быть эспрессированы в растениях с сохранением их природных иммунологических свойств. Так, клубни трансгенного картофеля, экспрессировавшие бактериальные антигены, стимулировали гуморальный и мукозный иммунные ответы при употреблении их в пищу. Хотя использование съедобных вакцин для предотвращения болезней еще не доказано, дальнейшее развитие этого направления может стать первым шагом на пути к созданию вакцин нового поколения.